2018
DOI: 10.1021/acsenergylett.8b00045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nonfullerene Acceptor Core Structure on the Photophysics and Efficiency of Polymer Solar Cells

Abstract: Small-molecule (SM) 'nonfullerene' acceptors are promising alternatives to fullerene (PC61/71BM) derivatives often used in bulk heterojunction (BHJ) organic solar cells; yet, the efficiency-limiting processes and their dependence on the acceptor structure are not clearly understood. Here, we investigate the impact of the acceptor core structure (cyclopenta-[2,1-b:3,4-b′]dithiophene (CDT) vs. indacenodithiophene (IDTT)) of malononitrile (BM)-terminated acceptors, namely CDTBM and IDTTBM, on the photophysical ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 45 publications
1
46
0
Order By: Relevance
“…[29] The calculation of exciton binding energy and reorganization energy was based on the B3LYP functional and the 6-31G(d) basis set, since B3LYP is one of the most widely used functional that has previously been shown to give results of molecular orbital levels, exciton and ionic states of NFAs that agree well with the measurements. [30][31][32][33][34] For example, the measured HOMO level and lowest-energy absorption peak of IT-IC are -5.51 eV and 1.75 eV, respectively, [6] as compared to -5.49 eV and 1.76 eV calculated using B3LYP. The exciton binding and reorganization energies of NFAs calculated using B3LYP are comparable with reported previously.…”
Section: Methodsmentioning
confidence: 86%
“…[29] The calculation of exciton binding energy and reorganization energy was based on the B3LYP functional and the 6-31G(d) basis set, since B3LYP is one of the most widely used functional that has previously been shown to give results of molecular orbital levels, exciton and ionic states of NFAs that agree well with the measurements. [30][31][32][33][34] For example, the measured HOMO level and lowest-energy absorption peak of IT-IC are -5.51 eV and 1.75 eV, respectively, [6] as compared to -5.49 eV and 1.76 eV calculated using B3LYP. The exciton binding and reorganization energies of NFAs calculated using B3LYP are comparable with reported previously.…”
Section: Methodsmentioning
confidence: 86%
“…Also, the effect of the MW of the acceptor in all‐polymer solar cells has been reported to influence the PCE . However, it is noteworthy that, until now, only a handful of studies have comprehensively reported time‐resolved studies of the photophysical processes in polymer:NFA systems …”
Section: Introductionmentioning
confidence: 99%
“…[27] However, it is noteworthy that, until now, only a handful of studies have comprehensively reported time-resolved studies of the photophysical processes in polymer:NFA systems. [28] In this work, four P3HT batches with different MWs (17,34,64, and 111 kDa) were used. The highest PCE was achieved for the intermediate MW system P3HT34K:O-IDTBR (6.6%), whereas the PCE gradually decreased for higher MWs, such as P3HT111K (4.4%), and for lower MW P3HT17K (4.0%).…”
Section: Introductionmentioning
confidence: 99%
“…3 However, these acceptors suffer from some drawbacks such as limited light absorption in the visible region, high cost, instability of surface morphology in the blend lms, difficulty in synthesis and purication and limited energy level tunability. 4,5 To overcome these challenges, there has been lot of reports in the recent literature on the design of nonfullerene based acceptors 6,7 with broader absorption, readily tunable energy levels, and ease of synthesis and purication. 8,9 Solution processable, non-fullerene bulk heterojunction (BHJ) solar cells with power conversion efficiencies (PCEs) > 8% have recently been reported which indicate the potential of nonfullerene electron acceptors.…”
Section: Introductionmentioning
confidence: 99%